PENGEMBANGAN MODUL AJAR OPERASI VEKTOR TERKAIT KEMAMPUAN PEMECAHAN MASALAH MATEMATIS BERBASIS PROBLEM BASED LEARNING - Resti Minarsi; Yayu Laila Sulastri; Luki Luqmanul Hakim (Universitas Islam Nusantara, 2022)
This research is motivated by the regulation of the Ministry of Education and Culture of the Republic of Indonesia which has issued a driving school program. The needs in the driving school program are the existence of teaching devices in the form of teaching modules to realize the profile of Pancasila students. In learning activities, students' mathematical problem solving skills are still low, one of the learning models to improve problem solving skills is the Problem-Based Learning model and students are still having difficulty solving vector material in vector sub operations, so it is necessary to develop a Vector Operations Teaching Module Related to Mathematical Problem Solving Ability Problem-Based Learning. The purpose of this study was to determine the validity of the teaching module, the effectiveness and practicality of the developed teaching module. The research method used in this study, namely Design Based Research with the Plomp model. Sources of data in this study are validators of material experts, media experts, and respondents. The instruments used are material expert validation sheets, media experts, ability tests, affective questionnaires, affective observations, psychomotor observations and educator response questionnaires. The data were analyzed using percentages which were interpreted according to their qualifications. Based on the results of the analysis, it can be concluded that the teaching module developed is very valid, effective, and practical. It is recommended that further research be carried out for large-scale trials, different materials or other mathematical abilities.